(NdELI(B: (NISTORIQ I KULXTURA (B/s - (Na[RAFQN(B, (NkLARA zARMAJROWNA(B.s; (NkOTOWSKIJ(B, (Ng(B.(Ng(B.s; (NiNSTITUT WOSTOKOWEDENIQ aKADEMII NAUK sssrs ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NWOST(B. (NLIT(B. ,s, 1987)
(NrEZ(B.: (NANGL(B.s
(NbIBLIOGR(B.: (NS(B. 257-261 ( 160 (NNAZW(B. )s
Keywords: (NdELIs -- (NiSTORIQs -- (NkULXTURAs; (NdELIs